Streptococcus pneumoniae IgA1 protease: A metalloprotease that can catalyze in a split manner in vitro. (23rd February 2017) - Chi, Ying‐Chih; Rahkola, Jeremy T.; Kendrick, Agnieszka A.; Holliday, Michael J.; Paukovich, Natasia; Roberts, Thomas S.; Janoff, Edward N.; Eisenmesser, Elan Z.
Abstract: IgA1 proteases (IgA1P) from diverse pathogenic bacteria specifically cleave human immunoglobulin A1 (IgA1) at the hinge region, thereby thwarting protective host immune responses. Streptococcus pneumoniae ( S. pneumoniae ) IgA1P shares no sequence conservation with serine or cysteine types of IgA1Ps or other known proteins, other than a conserved HExxH Zn‐binding motif (1604‐1608) found in metalloproteases. We have developed a novel expression system to produce the mature S. pneumoniae IgA1P and we have discovered that this form is both attached to the bacterial cell surface and released in its full form. Our data demonstrate that the S. pneumoniae IgA1P comprises two distinct regions that associate to form an active metalloprotease, the first such example of a metalloprotease that can be split in vitro and recombined to form an active enzyme. By capitalizing on this novel domain architecture, we show that the N‐terminal region of S. pneumoniae IgA1P comprises the primary binding region for IgA1, although the C‐terminal region of S. pneumoniae IgA1P is necessary for cleavage of IgA1. Our findings lend insight into the protein domain architecture of the S. pneumoniae IgA1P and function of this important virulence factor for S. pneumoniae infection.